Large-sized fossil hamsters from the late Middle Pleistocene Locality 2 of Shanyangzhai, China, and discussion on the validity of Cricetinus and C. varians (Rodentia: Cricetidae) - Xie, Kun; Zhang, Yunxiang; Li, Yongxiang (PeerJ, 2023)
A detailed morphological description and comparative study were conducted on numerous large-sized hamster remains collected from the late Middle Pleistocene Locality 2 of Shanyangzhai (Syz 2), Hebei Province, China. The comparisons reveal that these fossils are highly similar to the extant Tscherskia triton in size and morphology, including the small degree of alternating between the main opposite cusps on M1-3, the presence of axioloph on M3, and mesolophids on m1-2 that are present but seldom reach the lingual margin of the teeth, among other features. However, minor differences between the two still exist. Consequently, all these fossils are designated as a chronosubspecies of the extant species, T. triton varians comb. nov. The skull and molar morphologies of Cricetinus varians and T. triton were meticulously compared to resolve the long-standing debate regarding the validity of Cricetinus Zdansky, 1928 and C. varians Zdansky, 1928. The findings indicate that the differences between the two are slight; as a result, C. varians can only be considered a chronosubspecies of T. triton, i.e., T. triton varians comb. nov., and Cricetinus should be recognized as a junior synonym of Tscherskia. We tentatively propose that, among the seven species once referred to Cricetinus, C. europaeus, C. gritzai, C. janossyi, and C. koufosi should be reassigned to Tscherskia, while C. beremendensis should be transferred to Allocricetus, and C. mesolophidos to Neocricetodon. Excluding Tscherskia sp. from the Late Pliocene Youhe fauna, there are no reliable Tscherskia fossils in China earlier than the Middle Pleistocene. Based on the current evidence, Tscherskia may have originated from Neocricetodon during the Early Pliocene in Europe and subsequently spread to Asia. T. triton is its sole surviving representative, which now exclusively inhabits East Asia.
Keywords: Shanyangzhai fauna; Cricetinus varians; Tscherskia triton varians; Neocricetodon